Transformation of health communication literacy in the pandemic era - K. Y.S. Putri; Deddy Mulyana; S Bekti Istiyanto; Linda Zakiah; Rayni Delya Hafni (Universitas Negeri Yogyakarta, 2021)
Indonesian public health communication literacy is the education center for the government and related institutions. The formulation of this research problem is how to model health communication literacy in communities in tourism areas in Indonesia. The research objective was to determine the health communication literacy model in the community in tourism areas in Indonesia. The concept used in this research is new media literacy and health communication and audience attitudes. Several previous studies support this research. The method used is quantitative by distributing questionnaires to respondents. The result of the research is that health communication literacy on social media in a cognitive structure greatly affects the respondents. However, at the conative level, there are still some respondents who do not care about this pandemic because of the long duration. In the simple regression results, this study shows a great influence on the respondent's attitude. The suggestion of this research is the need for knowledge collaboration in subsequent research. So that it is not only in social science research but with natural science.